Ordering Aqiqah Package Products At Salam Aqiqah Medan In Accordance With Islamic Business Law - Alharis, Muhammad Rezy; Pinem, Rasta Kurniawati Boru (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
This research analyzes the practice of ordering aqiqah package products by Salam Aqiqah Medan as aqiqah service provider adopting a digital platform. Issues from an Islamic business law perspective include unclear ordering information, lack of consumer data protection, non-compliance with Shariah Aqiqah principles, and stock limitations. The research aims to evaluate unclear ordering information, analyze consumer data protection, assess compliance with Shariah principles, and address stock limitations. A qualitative method is used with observation, interviews, and documentary study. Findings indicate: 1. Unclear pricing involving vague calculation and determining factors. 2. Efforts towards transparency by Salam Aqiqah Medan, but consumer data privacy is a concern. 3. Salam Aqiqah Medan strives to adhere to Shariah Aqiqah principles, yet discrepancies between estimated product weight and post-slaughter actual weight raise concerns. 4. Stock limitations could lead to customer dissatisfaction and uncertainty. This research illustrates challenges and efforts Salam Aqiqah Medan faces in integrating aqiqah into the digital era, emphasizing transparency, Shariah compliance, and stock availability.